2022
DOI: 10.3390/jcm11041114
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Retrospective Study on Clinical Characteristics and Outcome of Pyogenic Liver Abscess Focusing Multidrug-Resistant Organisms

Abstract: The emergence of multidrug-resistant organisms (MDROs) is a growing problem worldwide. However, little is known about the incidence, clinical features and outcomes of pyogenic liver abscesses (PLAs) caused by MDROs. A retrospective study of 833 patients with PLA admitted from 2008 to 2017 was performed. MDROs were found in 55 (6.6%) patients, and extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae was the most common causative microorganism. To evaluate the clinical features of and risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Carbapenem-resistant K. pneumoniae (CRKP) was the most common of the carbapenem-resistant bacteria. A study conducted in South Korea [ 14 ] evaluated 833 patients with PLA from 2008 to 2017 and found that 6.6% of cases of PLA were caused by MDRO, which lower than the prevalence observed in this study. The presence of anaerobic bacteria and other rare pathogens may have been underestimated because conventional bacterial culture may not detect atypical pathogens.…”
Section: Discussioncontrasting
confidence: 81%
“…Carbapenem-resistant K. pneumoniae (CRKP) was the most common of the carbapenem-resistant bacteria. A study conducted in South Korea [ 14 ] evaluated 833 patients with PLA from 2008 to 2017 and found that 6.6% of cases of PLA were caused by MDRO, which lower than the prevalence observed in this study. The presence of anaerobic bacteria and other rare pathogens may have been underestimated because conventional bacterial culture may not detect atypical pathogens.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition, recent studies have reported a rapid increase in the incidence of PLA in Asia, especially Korea [ 7 , 11 ]. This phenomenon is known to be related to an increase in the numbers of older patients and patients with underlying diseases such as cancer, cirrhosis and chronic renal failure [ 7 , 10 ] and increasing infections with not only Klebsiella pneumoniae (K. pneumoniae ) [ 7 , 12 ] but also multidrug-resistant organisms [ 13 ]. In clinical settings, the initial recommended treatment for PLA is the use of empiric antibiotic regimens such as amoxicillin-clavulanic acid, third-generation cephalosporins combined with an aminoglycoside, or piperacillin/tazobactam [ 14 ].…”
Section: Introductionmentioning
confidence: 99%